Authenticated Tree-Based R-LWE Group Key Exchange. (24th October 2021) - Hougaard, Hector; Miyaji, Atsuko
Abstract: We present the first constant round, multicast, authenticated tree-based R-LWE group key exchange protocol with logarithmic communication and memory complexity. Our protocol achieves post-quantum security through a reduction to a Diffie–Hellman-like analogue to the decisional R-LWE problem. We also present a sequential version with constant memory complexity but a logarithmic number of rounds and communication complexity.